2020
DOI: 10.1002/aoc.5817
|View full text |Cite
|
Sign up to set email alerts
|

Electroreduction of Dy(III) assisted by Zn and its co‐deposition with Zn(II) in LiCl–KCl molten salt

Abstract: To recover dysprosium (Dy) from LiCl–KCl molten salt, the electrochemical mechanism of Dy(III) on liquid Zn electrode and co‐deposition of Dy(III) and Zn(II) on W electrode were studied using electrochemical methods. Cyclic voltammetry results demonstrated that the redox process of Dy on liquid Zn electrode is reversible and controlled by diffusion. Reverse chronopotentiograms showed that the transition time ratio of reduction and oxidation is ~3:1, revealing the redox of Dy on liquid Zn electrode is a kind of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The transition times of II c and II a are similar also implies that the reduction product of II c is insoluble. 31 When the oxidation time of Eu(II) increased and more Eu(III) was generated, the transition time of II c also increased. This phenomenon indicates that II c is attributed to the reduction of Eu(III).…”
Section: Resultsmentioning
confidence: 99%
“…The transition times of II c and II a are similar also implies that the reduction product of II c is insoluble. 31 When the oxidation time of Eu(II) increased and more Eu(III) was generated, the transition time of II c also increased. This phenomenon indicates that II c is attributed to the reduction of Eu(III).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is critical to recover and separate lanthanides from molten salt for nuclear fuel cycle and the purification of waste salts 29 . In recent years, the electrorecovery lanthanides from molten salt were explored on various electrodes, 30‐51 for example, Mg, 30 Al, 31‐34 Ni, 35,36 Cu, 37‐39 Bi, 40‐43 Zn, 38,39,44,45 Cd, 46,47 Sn, 48 Pb, 49‐51 and Ga 52 . Since there are some advantages to use low melting point metal as a liquid working electrode, many researchers paid more attentions to the electrochemical extraction using a liquid electrode.…”
Section: Introductionmentioning
confidence: 99%
“…14 Thus, liquid cathode is paid more attention because of its complete physical separation between the metal product and electrolyte, constant electrode area, and easy diffusion of deposited metal into liquid metal. Low melting metal and alloy, for example, Bi, [30][31][32] Sn, 33,34 Cd, 35,36 Pb, [37][38][39] Ga, 40,41 Zn 14,[42][43][44] metals and Al-Ga alloy [45][46][47] were explored as a liquid cathode. The feasibility of liquid metals (Sb, Bi, Pb, Sn, Ga) as cathode was systematically investigated in molten fluorides, Gibilaro et al found that the electroactivity domains and reactivity of liquid metals are Bi > Pb > Sn > Sb > Ga. 48 Lebedev 49 evaluated the separation factor between actinides and lanthanides on various cathodes in molten chlorides, and found that the separation order is Al > Ga > Pb > Zn > Bi > Sn > In > Cd > Tl.…”
mentioning
confidence: 99%